Pengaruh Persepsi dan Perilaku Konsumen terhadap Kepuasan Pelanggan di PT. Brani Lintas Samudera - Tifany, Tifany; Rustam, Triana Ananda (SEIKO : Journal of Management & Business, 2023)
In the era of globalization, competition between companies is getting more and more complicated so that each company is encouraged to fix everything related to the company so that it can continue to grow. This study aims to determine the effect of consumer perceptions, consumer behavior on customer satisfaction at PT Brani Lintas Samudera partially and simultaneously. The type of research determined in this study is quantitative research using descriptive research design. The research population was 102 customers at PT Brani Lintas Samudera. The technique used in this research is Non probability sampling technique, namely saturated sampling technique. The data in this study were collected by questionnaire and analyzed using the SPSS version 25 program. The tests used in this study are validity test, reliability test, normality test, multicollinearity test, heterokedasticity test, multiple linear regression, detemination coefficient (R2), t test and f test. The results showed that consumer perceptions and consumer behavior have a positive influence and partially affect customer satisfaction. The results of the f test show that consumer perceptions and consumer behavior simultaneously affect customer satisfaction at PT Brani Lintas Samudera. Kata Kunci: Persepsi; perilaku konsumen; kepuasan pelanggan.